Money as a measure of value ("Journal "U". Economy. Management. Finance.", 2024)
The article examines the concept of money as a measure of value, its historical development, functions and role in the modern economy. Special attention is paid to the theoretical aspects of money, including its properties and importance in economic activity. The article also addresses the issues of inflation, purchasing power and the international importance of currencies. The prospects for the development of the monetary system in the context of digitalization and globalization, including the influence of cryptocurrencies and digital currencies of central banks, are analyzed.
Keywords: money; measure of value; functions of money; purchasing power; inflation; currencies; digitalization; cryptocurrencies; economy